Human capital and regional growth in Switzerland - Wolfgang Polasek; Wolfgang Schwarzbauer; Richard Sellner (Institute for Advanced Studies (IHS), 2010)
This paper develops a regional production function model for Swiss cantons that incorporates human capital together with spatial effects. Within a spatial panel framework we find that controlling for time effects the spatial spillover effect becomes insignificant. Our results are sensitive with respect to the human capital proxy. We find that the share of academics in the workforce is the main component of human capital driving productivity growth in Swiss cantons. This is in line with findings of previous studies suggesting that mostly highly skilled workers matter for productivity growth in technologically advanced economies.
Keywords: C21; C23; I22; J23; R11; R12; 330; production function with human capital; spatial panel; regional growth; Humankapital; Regionales Wachstum; Produktionsfunktion; Teilstaat; Schweiz